Process and Outcomes of Collaborative Governance in Poverty Alleviation in Southwest Papua Province - Suroso, ‎; Ibrahim, Muh Akmal; Hasniati, ‎ (KnE Social Sciences, 2025)
Poverty is a major problem faced by the Government of Southwest Papua Province, which has the highest poverty rate in Indonesia. This research aims to analyze collaborative governance in poverty alleviation in Southwest Papua Province for which a qualitative approach was used. Data collection methods included observation, in-depth interviews, and documentation. Data sources consisted of primary and secondary data, while data analysis was conducted using the interactive method. The informants in this research are stakeholders who are directly involved in poverty alleviation policies in Southwest Papua Province. Based on the results, it was found that poverty alleviation was intervened by many Regional Device Organization (OPDs). Furthermore, the various OPDs were members of the Regional Poverty Reduction Acceleration Team (TKPKD). So far, poverty alleviation in West Papua Province has not optimally reduced the poverty rate. The main problems faced are related to the collaboration process between OPDs, including face-to-face dialogue that is not carried out regularly and periodically, so that synergy and mutual understanding between TKPKD members have not been well formed. In addition, TKPKD’s commitment has not been accompanied by joint action in implementing poverty alleviation programs, and its form is often still limited to verbal statements. As for the outcome, there has been a decrease in the percentage of the poverty rate, but the decrease is still above the average percentage of the national poverty rate.